+0  
 
+1
131
2
avatar+2487 

Help.

NotSoSmart  Jan 4, 2018
Sort: 

2+0 Answers

 #1
avatar+109 
+1

#17 {(4,0), (0,4)}

 

#18 3,-2,2

 

 

those are the answers

penquino21  Jan 4, 2018
 #2
avatar+86613 
+1

17

 

x  +  y   =  4  ⇒   y  =  4 - x     (1)

x^2  + y^2  =  16       (2)

 

Sub   (1)  into (2)  and we have that

 

x^2  + (4 - x)^2   =  16

x^2  +  (x - 4)^2  = 16

x^2  + x^2  - 8x  +  16  =  16      subtract 16 from both sides

 

2x^2  - 8x  = 0     factor

2x ( x   - 4)  = 0

 

Setting each factor to 0  we have that x  = 0   and x  = 4

And when x  = 0   , y  = 4 - 0  = 4

And when x = 4, y  = 4 - 4  = 0

 

So.....the solutions are    (0,4)  and (4,0)

 

 

18.....easy,  NSS

 

Just change the signs  on the constants in the parentheses and we get

 

3, -2 , 2

 

 

cool cool cool

CPhill  Jan 4, 2018

36 Online Users

avatar
avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy